Design of the Supporting Structures for Large and Unusually Shaped Foundation Pit near the Yangtze River - Shulan Guo; Changhong Yan; Liangchen Yu; Yang You (Advances in Civil Engineering)
A large underground transportation hub is located on the west side of the Nanjing Youth Olympic Center, which is close to the embankment of the Yangtze River. The near-surface primarily comprises newly deposited soft soil of considerable thickness; the lower part is a riverbed-phase sandy soil containing two confined aquifers. The foundation pit requires deep excavation and has unusual shapes of “pit in pit” and “pit leaning pit.” For the convenience and safety of excavation, the piezometric head of the upper confined aquifer, where the pit bottom is located, reached 1 m below the bottom plane through precipitation, while that of the lower confined aquifer also dewatered down to a safe water level to avoid an uplift problem. After considering the engineering geological conditions, the function and shape of the foundation pits, we divided the soil layers of the foundation pits into two areas (the NW area and the SE area) and proposed the support scheme correspondingly. The numerical simulation results and completed construction safely verified the feasibility of the support scheme.